TEACHERS' TECHNIQUES IN ADAPTING TEXTBOOK IN EFL CLASSROOMS: A Descriptive Study at One of Junior High Schools in Bandung - Junaedi, Ayu Hilda (2014)
This study investigated the difficulties in using textbook and textbook adaptation processes in EFL classrooms. The participants of the study were three English teachers in a junior high school in Bandung. The qualitative descriptive case study used as research design. This study used three techniques in collecting data: interview, document analysis and classroom observation. The findings revealed that there were four main difficulties faced by the teachers: grammatical errors in texts and dialogues, unavailability audio cassette for listening and speaking skills, incompatibility between syllabus and materials in the textbook and limited time for adapting textbook. Furthermore, the adaptation processes which were usually used by the teachers were modifying content, adding materials or tasks, extending material, addressing omission, re-ordering materials or tasks and reduction or simplifying the materials. The result of the study is expected to broaden teachers' knowledge about how to use textbook and do adaptation for teaching and learning processes. Studi ini meneliti tentang kesulitan dalam menggunakan buku teks dan proses adaptasi buku teks di kelas EFL (English Foreign Language). Responden dalam studi ini adalah tiga guru bahasa Inggris di salah satu sekolah menengah pertama di Bandung. Studi ini menggunakan deskriptif qualitatif. Studi ini menggunakan 3 teknik pengumpulan data: wawancara, analisis dokumen, dan observasi kelas. Dalam studi ini ditemukan empat kesulitan yang dihadapi guru: kesalahan tata bahasa di dalam teks dan dialog, tidak tersedia kaset untuk mendengarkan dan berbicara, ketidaksesuaian antara silabus dan materi yang ada di buku teks, dan tidak ada waktu dalam mengadaptasi buku. Dan proses adaptasi yang biasa digunakan oleh guru adalah memodifikasi, menambahkan materi atau latihan, memperpanjang materi, menghilangkan materi, menyusun ulang materi atau latihan, dan menyederhanakan materi. Hasil studi ini diharapkan dapat memperluas pengetahuan guru tentang bagaimana menggunakan buku teks dan melakukan adaptasi untuk proses belajar mengajar.